Policy Complementarities : The Case for Fundamental Labor Market Reform - Snower, Dennis (IMF Working Papers; Working Paper, 1996)
This paper argues that an important group of labor market policies are complementary in the sense that the effect of each policy is greater when implemented in conjunction with the other policies than in isolation. This may explain why the diverse, piecemeal labor market reforms in many European countries in recent years have had so little success in reducing unemployment. What is required instead is deeper labor market reforms across a broader range of complementary policies and institutions. To be politically feasible, these reforms must be combined with measures to address distributional issues.